Isolation and expression of heat shock protein 30 gene from Penicillium marneffei - Nongnuch Vanittanakom (2018)
Penicillium marneffei is a dimorphic fungus that can cause disseminated mycosis, especially in AIDS patients. The role of heat shock proteins and stress response-related proteins in P. marneffei remains unknown. In this study, we isolated a cDNA encoding for heat shock protein 30 (Hsp30) of P. marneffei using an antibody screening method. The DNA sequence and deduced amino acid sequence analysis showed high homology to other fungal hsp30 genes. Expression of P. marneffei hsp30 in response to temperature increase was determined by Northern blot analysis. A high level of hsp30 transcript was detected in yeast cells grown at 37°C, whereas a very low or undetectable transcript level was observed in mycelial cells at 25°C. A recombinant Hsp30 protein was produced and tested preliminarily for its immunoreactivity with sera from P. marneffei-infected AIDS patients using Western blot analysis. The positive immunoblot result, with some serum samples, confirmed the antigenic property of the Hsp30. Collectively, the high response of hsp30 to temperature increase could indicate it may play a role in heat stress response and cell adaptation. This is the first report showing that this small heat shock protein could elicit the human immune response. © 2009 ISHAM.